2004
DOI: 10.1007/s00015-004-1135-4
|View full text |Cite
|
Sign up to set email alerts
|

Earthquakes in Switzerland and surrounding regions during 2003

Abstract: this report of the swiss seismological service summarizes the seismic activity in switzerland and surrounding regions during 2008. During this period, 451 earthquakes and 75 quarry blasts were detected and located in the region under consideration. the three strongest events occurred in the Valais, near Lac des toules (M L 3.6), and in Graubünden, near Ilanz (M L 3.7) and Paspels (M L 4.0). Although felt by the population, they were not reported to have caused any damage. However, with a total of only 15 event… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
18
0
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 22 publications
3
18
0
1
Order By: Relevance
“…The average of these three rotation poles is [8.9E, 45.7N], located at the boundary between the Po Basin and the southern foothills of the Central Alps. This location of Adria's Euler pole is consistent with the aseismicity of the Lepontine Dome , the extensional and dextral seismotectonic regime in the Western Alps and in the Valais (Maurer et al, 1997, Deichmann et al, 2002, and with a compressional regime observed in seismotectonics and paleoseismology in the Eastern Alps, east of longitude 9.5°E (e.g. WORKING GROUP CPTI, 2004).…”
Section: Present-day Kinematicssupporting
confidence: 72%
“…The average of these three rotation poles is [8.9E, 45.7N], located at the boundary between the Po Basin and the southern foothills of the Central Alps. This location of Adria's Euler pole is consistent with the aseismicity of the Lepontine Dome , the extensional and dextral seismotectonic regime in the Western Alps and in the Valais (Maurer et al, 1997, Deichmann et al, 2002, and with a compressional regime observed in seismotectonics and paleoseismology in the Eastern Alps, east of longitude 9.5°E (e.g. WORKING GROUP CPTI, 2004).…”
Section: Present-day Kinematicssupporting
confidence: 72%
“…the 2001 activity took place exactly vertically below the well known carboniferous graben of salvan Dorenaz (Deichmann et al 2002). the strike of the active fault perfectly matches the strike of this graben (NE-sW).…”
Section: Alps Central Zone: Ac_01 To Ac_15 Small Scale Zonesmentioning
confidence: 59%
“…7. Depth distribution of well constrained small earthquakes of switzerland, projected onto a N-s profile across the Alps after Deichmann et al (2002). We superimposed a tentative interpretation in terms of temperature and lithology.…”
Section: Rhine Graben Rg_1 Rg_2 and Rg_3 Small Scale Zonesmentioning
confidence: 99%
“…5). This transcurrent dextral fault system runs from the Aiguilles Rouges strike-slip fault, possibly connected north-eastward with the dextral seismic alignment of the northern Valais (Deichmann et al 2002), towards the southern front of the Belledonne massif (Thouvenot et al 2003) up to the High-Durance and Bersézio/Argentera faults Southeastward (Sue et al 1999;Sue & Tricart 2003).…”
Section: Discussion -Comparison With Seismotectonicsmentioning
confidence: 96%